Ionic and poly(ionic liquid)s as perovskite passivating molecules for improved solar cell performances. Issue 43 (1st November 2022) - Mariotti, Silvia; Mantione, Daniele; Almosni, Samy; Ivanović, Milutin; Bessho, Takeru; Furue, Miwako; Segawa, Hiroshi; Hadziioannou, Georges; Cloutet, Eric; Toupance, Thierry
Abstract : Ionic liquids and poly(ionic liquid)s act as bulk and/or passivation agents when used as additives in methylammonium-free lead perovskites, leading to devices showing enhanced power conversion efficiencies, reduced hysteresis and improved stability. Abstract : Perovskite solar cell devices have improved significantly in efficiency and are on the verge of commercialization. However, device stability has not yet been fully met. In this study, we use a K + -doped formamidinium (FA)-based perovskite, which has been shown to be an ideal perovskite for fabricating efficient solar cells with low hysteresis and better stability compared to MA-free perovskite materials. Nevertheless, in order to further progress on the performance and stability of the devices, additives were employed. While in the literature different types of additives have been used, in particular ionic liquids (ILs) and polymers, the novelty of this work lies in the use of poly(ionic liquid)s (PILs) as additives for the absorber layer, which have been used only recently as perovskite passivation agents. PILs were chosen for their high ionic conductivity and their hydrophobic nature in a macromolecular structure. Here, we show a direct comparison between the performances of devices obtained by adding a passivation IL (tBMPy-TFSI) and its polymeric version PIL (PVMPy-TFSI) in the perovskite layer. Preliminary studies show that the addition of both additives improves the solar cell performance and reduces the degradation rate. In particular, while the IL mainly induces higher solar cell performances due to the increase in V OC and FF, the PIL promotes J SC and performance stability under illumination and significantly reduce the J – V hysteresis index, to approach 0% under AM1.5G illumination. Thus, both ILs and PILs are valuable passivation molecules for perovskite grain boundaries, promoting charge diffusion and protecting the perovskite layer from external agents that may induce degradation. We believe that PIL additives present attractive prospects for stable perovskite solar cell devices.